2023
DOI: 10.3390/nu15163616
|View full text |Cite
|
Sign up to set email alerts
|

Folate Deficiency Enhanced Inflammation and Exacerbated Renal Fibrosis in High-Fat High-Fructose Diet-Fed Mice

Chun-Wai Chan,
Bi-Fong Lin

Abstract: The prevalence of obesity and chronic kidney disease (CKD) is increasing simultaneously and rapidly worldwide. Our previous study showed that folate deficiency increased lipid accumulation and leptin production of adipocytes. Whether folate plays a role in CKD, particularly obesity-related nephropathy remains unclear. To investigate the effects of folate deficiency on CKD in diet-induced obese mice, four groups of male C57BL/6 mice were fed either a normal-fat diet (NF) with folate (NF+f); NF without folate (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…10 Folate is an important substance required in the synthesis of DNA and RNA, which can avoid the destruction of intracellular DNA, reduce oxidative stress, prevent cell apoptosis, and play an important role in cell growth, differentiation, and repair. 11 Studies have found that long-term folate deficiency can cause obesity and glucose and lipid metabolism disorders, 12,13 and abnormal glucose and lipid metabolism is closely related to bone loss. 14 At the same time, some studies have shown that folate can significantly improve bone density and bone mass, 15,16 and there may be a certain relationship between folate and BMD.…”
Section: Introductionmentioning
confidence: 99%
“…10 Folate is an important substance required in the synthesis of DNA and RNA, which can avoid the destruction of intracellular DNA, reduce oxidative stress, prevent cell apoptosis, and play an important role in cell growth, differentiation, and repair. 11 Studies have found that long-term folate deficiency can cause obesity and glucose and lipid metabolism disorders, 12,13 and abnormal glucose and lipid metabolism is closely related to bone loss. 14 At the same time, some studies have shown that folate can significantly improve bone density and bone mass, 15,16 and there may be a certain relationship between folate and BMD.…”
Section: Introductionmentioning
confidence: 99%